2008
DOI: 10.5424/sjar/2008064-367
|View full text |Cite
|
Sign up to set email alerts
|

Short communication. Effect of deficit irrigation on curly lettuce grown under semiarid conditions

Abstract: Field experiments were conducted to characterize the effects of deficit irrigation on curly lettuce (Lactuca sativa var. Crispa cv. Bohemia) evapotranspiration, water use efficiency, marketable yield, yield components and mineral contents. The experiments were performed under semiarid climatic conditions in Erzurum province (east of Turkey) in the summer periods of 2005 and 2006. Irrigation water levels were selected to be 100% of usable soil water in full irrigation treatment (control) (T-100) and 80%, 60%, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 14 publications
5
11
0
Order By: Relevance
“…5 and 7). The results are, therefore, consistent with previously reported work on Ca translocation, transpiration, and tip burn (Choi and Lee, 1999; Gallardo et al, 1996; Kuslu et al, 2008; Molina‐Montenegro et al, 2011; Napier and Combrink, 2005; Palencia et al, 2010; Saure, 2005).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…5 and 7). The results are, therefore, consistent with previously reported work on Ca translocation, transpiration, and tip burn (Choi and Lee, 1999; Gallardo et al, 1996; Kuslu et al, 2008; Molina‐Montenegro et al, 2011; Napier and Combrink, 2005; Palencia et al, 2010; Saure, 2005).…”
Section: Resultssupporting
confidence: 92%
“…The results of this study are, therefore, consistent with the literature (Karam et al, 2002; Coelho et al, 2005; Kuslu et al, 2008; Capra et al, 2008; Mansuroğlu et al, 2011; Bozkurt et al, 2009; Bozkurt and Mansuroğlu, 2011) concerning the importance of eliminating root water uptake deficit by managing irrigation to meet 100% of the ET demand. The results are also consistent with the general understanding that Ca‐related physiological disorders are associated with short periods of limited Ca 2+ supply to the plant, which is itself associated with limited water fluxes.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Some researchers determined similar ET values with our results. Kuslu et al (2008) found average 232.3 mm ET value for fully irrigated curly lettuce in Erzurum, Turkey. Kadayifci et al (2004) obtained that ET of fully irrigated lettuce was 285 mm under greenhouse conditions.…”
Section: Discussionmentioning
confidence: 83%
“…from rainfall events, which cannot be controlled) can also have a significant impact on lettuce shelf life, increasing both caffeic acid levels and PAL and PPO activity, resulting in increased browning in processed lettuce (Luna et al 2012). Irrigation can also have a large effect on the mechanical properties of the lettuce leaf by influencing cell expansion and tissue turgor pressure (Kuslu et al 2008). Higher relative water content in whole head tissue at harvest increases susceptibility to damage during processing and subsequent pinking development.…”
Section: Watermentioning
confidence: 99%